Machu Picchu - Richardson, G. (2018)
Hidden by thick forest plants high in the Andes Mountains of South America, the Inca city of Machu Picchu lay abandoned for nearly 400 years. It was not until 1911 that it became active again. Find out more in Machu Picchu, a title in the Structural Wonders of the World series. These books identify some of the worlds best-known structures, exploring their history, the people responsible for their creation, and the science behind their construction. Each title features informative text, colorful photographs and maps, and a timeline detailing the steps toward construction.
Ages 7-11